2010
DOI: 10.1177/147323001003800109
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Digital and Anatomical Techniques in Skull Base Measurement

Abstract: This study compared the accuracy of measurements of the skull base made using computed tomography (CT) images and an image-guided surgery system with those made using scientific callipers in order to evaluate the practicability of replacing conventional direct anatomical measurements with digitized techniques in skull base surgery. Important bony landmarks and parameters were measured using the three different methods in 25 cadaver skull bases. No statistically significant differences were observed between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…For example, the difference between the measured lengths and the actual lengths was 0.08 mm for the anterior neck referent compared with 1.72 mm for the lateral neck referent. These results compare well with measurement accuracy reported in other studies of radiographic image measurement, such as in conventional and digital radiography (1.5 and 1.0 mm, respectively) [22], indirect and direct computed radiography (1.4 and 2.6 mm, respectively) [23], and CT imaging of the skull base (1 mm) [24].…”
Section: Discussionsupporting
confidence: 88%
“…For example, the difference between the measured lengths and the actual lengths was 0.08 mm for the anterior neck referent compared with 1.72 mm for the lateral neck referent. These results compare well with measurement accuracy reported in other studies of radiographic image measurement, such as in conventional and digital radiography (1.5 and 1.0 mm, respectively) [22], indirect and direct computed radiography (1.4 and 2.6 mm, respectively) [23], and CT imaging of the skull base (1 mm) [24].…”
Section: Discussionsupporting
confidence: 88%
“…Most studies present results comparing digital images with conventional radiographs (17)(18)(19)(20). In a similar way, our findings indicated that the digitized images analyzed with UThSCSa image Tool software facilitated measurements.…”
Section: Discussionsupporting
confidence: 66%
“…Sections across given levels could be precisely set to ensure standardization for further analysis among different models. Volumes, areas, angles, and distances can be accurately measured (30). In the of surgery simulation, the three-dimensional perspective and rotation freedom of the models could give the researchers a good sense of space and help them to build a positional relationship among critical structures (31)(32)(33).…”
Section: Priority and Shortcomings Of The Digital Model In Anatomic A...mentioning
confidence: 99%